Rearrangements in some species groups of Amblycerus Thunberg, 1815 (Coleoptera: Chrysomelidae: Bruchinae) including keys, description of a new species, new host plant and distributional records - Santos, Aluska Tavares Dos; Ribeiro-Costa, Cibele Stramare (Zootaxa, 2019)
Encompassing 39 species groups, Amblycerus Thunberg, 1815 is the second most diverse genus of seed-beetles in the Americas. Considering that the delimitation of some of the included species-groups is incongruent in the literature, this work tackled one particularly problematic group, the dispar group, which includes species that, depending on the classification scheme, have been classified in two other groups, namely the spondiae and alternatus groups. We recognize six valid species in the dispar group, viz. A. dispar (Sharp, 1885), A. crassipunctatus Ribeiro-Costa, 1999c A. insuturatus (Pic, 1902), A. schwarzi Kingsolver, 1970, A. taeniopygus Ribeiro-Costa, 1999 c, and Amblycerus goianiensis Santos & Ribeiro-Costa, sp. n., and four in the spondiae group, viz. A. spondiae Kingsolver, 1980, A. cuernavacensis Romero, Johnson & Kingsolver, 1996, A. vitis (Schaeffer, 1907) and A. alternatus (Pic, 1954). Three species are excluded from their original groups, namely A. eustrophoides (Schaeffer, 1904), A. serieguttatus (Chevrolat, 1877), from the alternatus group, and A. simulator (Jacquelin DuVal, 1857), from the dispar group, all considered here as incertae sedis. The remaining species of the alternatus group, A. schwarzi and A. alternatus, are transferred to other previously mentioned groups, thus dissolving this group. We provide diagnoses for the 13 species studied, redescribe three species, and describe one new species. Color illustrations of the dorsum and pygidium, drawings of the male genitalia and geographic distribution maps are included. Identification keys are also added for the dispar and spondiae groups. We record new host plants for four Amblycerus species and new localities for five species. The plant taxa Sarcomphalus mistol (Griseb.) Hauenschild, Terminalia corrugata (Ducke) Gere & Boatwr., T. tetraphylla (Aubl.) Gere & Boatwr. and Rhus virens Lindh. ex A. Gray var. choriophylla (Wooton & Standl.) L. D. Benson are first registered here as hosts of Amblycerus. Four new records for Amblycerus, namely Capparis, Neopringlea, Rhus and Sarcomphalus, and two new records at the family level, Capparaceae A. Juss. and Salicaceae Mirb., the latter also being a new record for Bruchinae.